2007
DOI: 10.1590/s0100-879x2006005000186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 30 mCi radioiodine on multinodular goiter previously treated with recombinant human thyroid-stimulating hormone

Abstract: Recombinant human thyroid-stimulating hormone (rhTSH) enhances 131 I uptake, permitting a decrease in radiation for the treatment of multinodular goiter (MNG). Our objective was to evaluate the safety and efficacy of a single 0.1-mg dose of rhTSH, followed by 30 mCi 131 I, in patients with MNG. Seventeen patients (15 females, 59.0 ± 13.1 years), who had never been submitted to 131 I therapy, received a single 0.1-mg injection of rhTSH followed by 30 mCi 131 I on the next day. Mean basal thyroid volume measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 31 publications
6
39
0
Order By: Relevance
“…This observation is in line with previous studies (9,10,12). Consequently, patients with a low RAIU benefit the most from rhTSH stimulation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This observation is in line with previous studies (9,10,12). Consequently, patients with a low RAIU benefit the most from rhTSH stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…Because the effect of rhTSH is highly dependent on the stable iodine load (21) and, especially, the baseline RAIU-but also to some extent on rhTSH dose-comparing this result with previous studies of NMG patients is difficult. In previous studies (9)(10)(11)(12)(13)22), an increase in 24-h RAIU between 68% and 335% was found using rhTSH doses from 0.01 to 0.45 mg. This considerable variation can mainly be attributed to differences in baseline RAIU (12%233%) and to the dose of rhTSH used.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, measurements of RAIU are extremely prone to variation in the method used. Despite these shortcomings, studies in MNG patients (19,20,40,(43)(44)(45)(46) and healthy individuals (41,42,47) document an approximately twofold increase in RAIU, largely independent of rhTSH dose. In support of this observation, a small comparative trial found that 0.03 mg was not superior to 0.01 mg (40) and another comparative trial observed that 0.3 mg was not superior to 0.1 mg (45).…”
Section: Radioiodine Therapy With Rhtsh Pre-stimulationmentioning
confidence: 99%
“…The remaining non-controlled studies (Table 2) have demonstrated considerable GVR between 35 and 53% (20, 43, 44, 46, 52, 53), 6-12 months after rhTSHaugmented 131 I therapy. Although lacking a control group, the results are promising since some of the latter studies (43,46) were carried out in patients with relatively low baseline RAIU, thus demonstrating the feasibility of 131-I therapy in such patients when employing rhTSH. One study, in 18 MNG patients with a baseline RAIU of 12%, documented a mean GVR of 39% after 6 months and 53% after 2 years (43, 54).…”
Section: Effect On Gvrmentioning
confidence: 99%